Increased severity of suicidal behavior in impulsive aggressive patients exposed to familial adversities. Issue 14 (October 2014) - Lopez-Castroman, J.; Jaussent, I.; Beziat, S.; Guillaume, S.; Baca-Garcia, E.; Genty, C.; Olié, E.; Courtet, P.
<x content-type="archive" xml:space="preserve">Abstract</x> Background The mechanisms by which childhood abuse and family history of suicidal behavior (FHS) lead to an increased risk of suicidal behavior are still unknown. Impulsive aggression may play an intermediate role. We investigated whether greater scores for aggression and impulsivity might be associated with the effects of FHS and/or childhood abuse on the severity of suicidal behavior. Method We examined the scores of three scales measuring impulsive aggression in a sample of 696 suicide attempters. We compared the highest and lowest scores with regard to reports of childhood abuse and FHS using adjusted multinomial regression models. Genetic polymorphisms of the serotonergic system known to be associated with impulsive aggression were also analyzed. Results Patients with high impulsive aggressive scores showed significant differences in sociodemographic, clinical and suicidal features compared with patients with low impulsive aggressive scores. Adjusted results showed that combinations of some types of childhood abuse and FHS, particularly emotional abuse and emotional neglect, are associated with high impulsivity and hostility scores. The SS genotype of the serotonin transporter gene (5-HTTLPR) was associated with high levels of impulsivity when the subjects reported emotional abuse [odds ratio (OR) 5.55, 95% confidence interval (CI) 1.75–17.5] or physical abuse (OR 5.03, 95% CI 1.50–16.9) in their childhood. Conclusions Our results support the role of impulsive aggression as one of the links that may connect childhood abuse and FHS with severity of suicidal behavior.